Essentials of paralegalism - William P. Statsky (Thomson Delmar Learning, 2006)
Essentials of Paralegalism introduces the beginning paralegal student to this still relatively new legal career. It presents the main regulatory and employment issues in the field, as well as strategies for finding a job. The author also gives students the basic skills they will need to succeed in the field including interviewing, investigation and analysis at an introductory level. Concrete examples from the working lives of on-the-job paralegals help the students get a feel for what they can expect in the work setting